The smoke of the gods : a social history of tobacco - Burns, Eric (Temple University Press, 2007)
Fox New Watch host Eric Burns, who chronicled the social history of alcohol in The Spirits of America turns to tobacco in The Smoke of the Gods. Ranging from ancient times to the present day, The Smoke of the Gods is a lively history of tobacco, especially in the United States. Although tobacco use is controversial in the U.S. today, Burns reminds us that this was not always the case. For centuries tobacco was generally thought to have medicinal and even spiritual value. Most of the signers of the Declaration of Independence were tobacco users or growers, or both. According to Burns, tobacco changed the very course of U.S. history, because its discovery caused the British to support Jamestown, its struggling New World colony. An entertaining and informative look at a subject that makes daily news headlines, The Smoke of the Gods is a history that is, well, quite addictive.